Askify – AI Driven Smart Questioning System - Sasikala, P.; Krishna, B. Sanjay; Lakshana, R.; Dharshini, B. Loga Priya; Sri, S. Nandhika; Netra, R. (International Journal of Research in Interdisciplinary Studies, 2025)
This paper presents the project titled “Askify,” a smart question collection and assessment creation system designed to help educators, trainers, and learners efficiently create, manage, and share question sets. The main objective of Askify is to transform raw subject notes and learning materials into organized and reusable question collections. In many educational environments, valuable study content remains unused due to the absence of proper tools for organizing and reusing questions. Askify addresses this problem by enabling users to import or upload notes, organize questions into collections, search and filter them by topic and difficulty level, preview and edit individual questions, and perform bulk actions. The system allows curated question sets to be exported in formats such as PDF and Excel for printing or sharing. With simple workflows and a user-friendly interface, Askify helps users quickly convert unstructured materials into ready-to-use quizzes, practice packs, and shared study lists.